Implementation of Green Practice in the Food and Beverage Department at Jimbaran Puri, A Belmond Hotel Bali - Ni Kadek Bella Puspitayanti; I Gusti Putu Sutarma; Lien Darlina; I Wayan Basi Arjana; I Nyoman Cahyadi Wijaya (The Postgraduate School of Tourism Sahid Polytechnic, 2024)
Purpose: This research aims to analyze the implementation of Green Practices in the Food and Beverage Department at Jimbaran Puri, A Belmond Hotel Bali, and the most dominant Green Practice indicators. Research methods: The data collection methods used are observation, interviews, questionnaires, and other supporting data. This research uses qualitative descriptive and quantitative descriptive analysis techniques. Results and discussion: The average indicator value for implementing Green Practice is four or implemented well. Based on the Green Practice Implementation Index calculation in the Food and Beverage Department at Jimbaran Puri, A Belmond Hotel, Bali, the result was 4.5. It has been implemented daily to create a sustainable, preservative Surrounding environment. Implication: From the percentage results of the three green practice indicators, green actions obtained a score of 26.62 percent, green food obtained a score of 9.35 percent, and green donations obtained a score of 9.09 percent. Based on the three green practice indicators, namely green action, green food, and green donation, it can be seen from the total score that the percentage is more significant for green action. Keywords: Implementation, Green Practice, Green Action, Green Food, Green Donation.